E3 ubiquitin ligase gene BIRC3 modulates TNF-induced cell death pathways and promotes aberrant proliferation in rheumatoid arthritis fibroblast-like synoviocytes - Meng, Qingliang; Wei, Kai; Shan, Yu (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by synovitis, degradation of articular cartilage, and bone destruction. Fibroblast-like synoviocytes (FLS) play a central role in RA, producing a significant amount of inflammatory mediators such as TNF-α and IL-6, which promote inflammatory responses within the joints. Moreover, FLS exhibit tumor-like behavior, including aggressive proliferation and enhanced anti-apoptotic capabilities, which collectively drive chronic inflammation and joint damage in RA. TNF is a major pro-inflammatory cytokine that mediates a series of signaling pathways through its receptor TNFR1, including NF-κB and MAPK pathways, which are crucial for inflammation and cell survival in RA. The abnormal proliferation and anti-apoptotic characteristics of FLS in RA may result from dysregulation in TNF-mediated cell death pathways such as apoptosis and necroptosis. Ubiquitination is a critical post-translational modification regulating these signaling pathways. E3 ubiquitin ligases, such as cIAP1/2, promote the ubiquitination and degradation of target proteins within the TNF receptor complex, modulating the signaling proteins. The high expression of the BIRC3 gene and its encoded protein, cIAP2, in RA regulates various cellular processes, including apoptosis, inflammatory signaling, immune response, MAPK signaling, and cell proliferation, thereby promoting FLS survival and inflammatory responses. Inhibiting BIRC3 expression can reduce the secretion of inflammatory cytokines by RA-FLS under both basal and inflammatory conditions and inhibit their proliferation. Further research into the specific mechanisms of BIRC3, including its roles in cell signaling, apoptosis regulation, and immune evasion, is crucial for identifying new therapeutic targets and strategies.